The chemistry and pharmacology of Ligularia przewalskii: A review. (12th June 2018) - Liu, Shi-Jun; Tang, Zhi-Shu; Liao, Zhi-Xin; Cui, Chun-Li; Liu, Hong-Bo; Liang, Yan-Ni; Zhang, Yu; Xu, Hong-Bo; Zhang, Dong-Bo; Zheng, Ya-Ting; Shi, Huan-Xian; Li, Shi-Ying
Abstract: Ethnopharmacological relevance: Ligularia przewalskii (Maxim.) Diels ( LP ) (called zhangyetuowu in Chinese), is generally found in moist forest areas in the western regions of China. The root, leaves and flower of LP are utilized as a common traditional medicine in China. It has been utilized conventionally in herbal remedies for the remedy of haemoptysis, asthma, pulmonary phthisis, jaundice hepatitis, food poisoning, bronchitis, cough, fever, wound healing, measles, carbuncle, swelling and phlegm diseases. Aim of the study: The review aims to provide a systematic summary of LP and to reveal the correlation between the traditional uses and pharmacological activities in order to provide updated, comprehensive and categorized information and identify the therapeutic potential for its use as a new medicine. Materials and methods: The relevant data were searched by using the keywords " Ligularia przewalskii " "phytochemistry", "pharmacology", "Traditional uses", and "Toxicity" in "Scopus", "Scifinder", "Springer", "Pubmed", "Wiley", "Web of Science", "China Knowledge Resource Integrated databases (CNKI)", "Ph.D." and "M.Sc. dissertations", and a hand-search was done to acquire peer-reviewed articles and reports about LP . The plant taxonomy was validated by the databases "The Plant List", "Flora Reipublicae Popularis Sinicae", "A Collection of Qinghai Economic Plants", "Inner Mongolia plant medicine Chi", Zhonghua-bencao and the Standard of Chinese herbal medicine in Gansu. Results: Based on the traditional uses, the chemical nature and biological effects of LP have been the focus of research. In modern research, approximately seventy-six secondary metabolites, including thirty-eight terpenoids, nine benzofuran derivatives, seven flavonoids, ten sterols and others, were isolated from this plant. They exhibit anti-inflammatory, antioxidative, anti-bacterial and anti-tumour effects, and so on. Currently, there is no report on the toxicity of LP, but hepatotoxic pyrrolizidine alkaloids (HPA) were first detected with LC/MS n in LP, and they have potential hepatotoxicity. Conclusions: The lung-moistening, cough-relieving and phlegm-resolving actions of the root of LP are attributed to the anti-inflammatory properties of flavonoids and terpenoids. The heat-clearing, dampness-removing and gallbladder-normalizing (to cure jaundice) actions of the flowers of LP are based on the anti-inflammatory, antioxidant and hepatoprotective activity properties of terpenoids, flavonoids and sterols. The Traditional Chinese Medicine (TCM) characteristics of LP (bitter flavour) corroborate its potent anti-inflammatory effects. In addition, the remarkable anti-inflammatory and antioxidant capacities of LP contribute to its anti-tumour and antitussive activities. Many conventional uses of LP have now been validated by modernized pharmacological research. For future research, further phytochemical and biological studies need to be conducted on LP, In particular, the safety, mechanism of action and efficacy of LP could be of future research interest before beginning clinical trials. More in vivo experiments and clinical studies are encouraged to further clarify the relation between traditional uses and modern applications. Regarding the roots, leaves and flowers of LP, their chemical compositions and clinical effects should be compared. The information on LP will be helpful in providing and identifying its therapeutic potential and economic value for its use as a new medicine in the future. Graphical abstract: fx1